2005
DOI: 10.7863/jum.2005.24.9.1289
|View full text |Cite
|
Sign up to set email alerts
|

Decidualization of Ovarian Endometriosis During Pregnancy Mimicking Malignancy

Abstract: This phenomenon is a diagnostic challenge and should be considered in the differential diagnosis of a malignant mass during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
47
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 10 publications
(13 reference statements)
2
47
0
1
Order By: Relevance
“…Furthermore, both malignancy and deciduosis are characterized by marked vascularization as observed on color or power Doppler sonography, and both may produce similar ovarian cystic masses with an irregular internal surface with excrescences and solid components. 18 The decidualized tissue within the cysts undergoes thickening of the stroma and gains an extensive blood supply, thereby acquiring the sonographic appearance of a malignant pelvic tumor. 18 However, in our 2 cases, there was no or very little blood supply seen on color Doppler sonograms, suggesting that deciduosis may be characterized by a markedly lower degree of vascularization compared with ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, both malignancy and deciduosis are characterized by marked vascularization as observed on color or power Doppler sonography, and both may produce similar ovarian cystic masses with an irregular internal surface with excrescences and solid components. 18 The decidualized tissue within the cysts undergoes thickening of the stroma and gains an extensive blood supply, thereby acquiring the sonographic appearance of a malignant pelvic tumor. 18 However, in our 2 cases, there was no or very little blood supply seen on color Doppler sonograms, suggesting that deciduosis may be characterized by a markedly lower degree of vascularization compared with ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…18 The decidualized tissue within the cysts undergoes thickening of the stroma and gains an extensive blood supply, thereby acquiring the sonographic appearance of a malignant pelvic tumor. 18 However, in our 2 cases, there was no or very little blood supply seen on color Doppler sonograms, suggesting that deciduosis may be characterized by a markedly lower degree of vascularization compared with ovarian cancer. Due to the hypertrophy of the ectopic endometrial stromal cells by decidual change during pregnancy, the diagnostic accuracy even of modern imaging modalities is limited, because functional decidual changes including contrast enhancement might be present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decidualization occurs not only in the uterine but also in the extrauterine endometrium during pregnancy [1,4,6] , especially in endometrial stromal cells of ovarian endometriotic cysts [1,4] . This study revealed that decidualized ovarian endometriotic cysts showed papillary excrescences mimicking malignancy during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the available publications concerning the problem of scar endometriomas do not focus on the cesarean section itself (e.g. indications or obstetrical state before and during the cesarean section) [5,7,8,10,[27][28][29][30][31][32][33][34] , some specify the indications for the cesarean section [35] , while in others only simple elective cesarean section can be found [36] .…”
Section: Discussionmentioning
confidence: 99%